IMPLEMENTASI PENDEKATAN MATEMATIKA REALISTIK DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA (SUATU TINJAUAN PUSTAKA) - Ricky Sanputra Sinaga (MES: Journal of Mathematics Education and Science, 2022)
This study aims to identify the tendency of research journal articles on Realistic Mathematics Education in improving students' critical thinking skills and identify journal articles and the potential impact of research on Realistic Mathematics Education in developing students' critical thinking skills. The form of the survey used is a descriptive qualitative research method of literature conducted at the Digital Library of Medan State University. The data analysis technique used is the Miles and Huberman model, which includes data reduction, data visualization, and inference (conclusion). The results of the study identified that articles and research trends were problems faced by researchers regarding the low critical thinking skills of students. This can be seen from several studies which show that there are some students who are not able to solve mathematical problems which is characterized by the tendency of students not to react to what the teacher and peers say during the learning process. The practical mathematical approach has a positive effect on students' critical thinking skills as evidenced by the average N-Gain value in each study.